Analisis Promosi Jabatan Dan Pengembangan Karir Pegawai Pada TVRI Sumatera Selatan - Desi Hamidah; Wiwin Agustian (STIKes Ibnu Sina Ajibarang, 2024)
The purpose of this study is to find out how to promote positions and career development for TVRI South Sumatra employees. This research uses descriptive qualitative. The subjects of this research are: 1) Field Program & Business Balancing. 2) Head of Engineering Field. 3) Head of Chief. Biidang Beiriita. 4) Chief. General Affairs. The method used in this research is descriptive method. Data collection techniques are observation techniques, interviews, interview guidelines and documentation. data collection tools are observation sheets, interview guides and documentation. Data management is carried out using qualitative descriptive analysis. The results of this study indicate that promotion and career development have a positive impact on performance improvement.